(untitled) (International Journal of Engineering and Computer Science, 2017)
The evaluation of the image quality is very important. The best subjective evaluation of the image is done by the human eyes as they are the good receivers. Objective analysis of the image is done by using full reference metric. The results of the objective measurements are validated by the subjective measurements. The objective evaluation of image in this paper has been done using PSNR (Peak Signal to Noise Ratio), MSE (Mean Squared Error) and SSIM (Structural Similarity Index Metric). These algorithms are applied on the different images. If the value of PSNR increases, the corresponding value of SSIM also increases and the value of MSE decreases. In the proposed wok, if the value of MSE increases by 8%, then the corresponding PSNR decreases by 10%. This is not applicable on all images because the MSE, PSNR and SSIM changes according to the complexity of the image. Every image has different coefficient of complexity. More complex image gets distorted first than the less complex image.